Ethnic differences in healthcare trust and patient satisfaction in England: A cross-sectional survey - Steven David Pickering; Martin Ejnar Hansen; Han Dorussen; Jason Reifler; Thomas Scotto; Yosuke Sunahara; Dorothy Yen (PLoS ONE, 2026)
Trust in healthcare is an important component of patient experience, yet ethnic minority patients in England often report lower trust and satisfaction with the NHS than White patients. We examine these differences using data from a cross-sectional survey of 1,111 adults living in England, conducted in April–May 2023. Respondents rated their agreement with 18 statements covering five domains of healthcare experience: communication, ethical treatment, perceived competence, trust in providers, and perceived discrimination. We estimate a series of linear regression models comparing responses between ethnic minority and White participants, both before and after adjustment for demographic and attitudinal factors. Ethnic minority respondents reported significantly less positive perceptions on several items, particularly those relating to ethical behaviour, personal care, trust in front-line providers and perceived discrimination. They were less likely than White respondents to agree that the NHS behaves ethically, cares for patients, or goes out of its way to help people, and reported lower trust in GPs and hospital doctors and nurses. The largest differences were observed for perceptions that NHS care quality depends on ethnic background or country of origin. By contrast, we found no ethnic differences in perceptions of NHS honesty, promise-keeping, overall competence, or trust in NHS leadership or management. Overall, the findings indicate that ethnic differences in trust and satisfaction with the NHS are concentrated in relational and experiential aspects of care rather than in assessments of technical competence. Addressing these disparities may be important for improving equity and strengthening trust in healthcare services.